Risk‐Neutral Parameter Shifts and Derivatives Pricing in Discrete Time - SCHRODER, MARK (Journal of Finance, 2004)
ABSTRACT We obtain a large class of discrete‐time risk‐neutral valuation relationships, or “preference‐free” derivatives pricing models, by imposing a simple restriction on the state‐price density process. The risk‐neutral stock‐return and forward‐rate dynamics are obtained by changing only a location parameter, which can be determined independent of the preference and true location parameters. The Gaussian models of Rubinstein (1976) , Brennan (1979) , and Câmera (2003) , and the gamma model of Heston (1993) are all special cases. The model provides simple relationships between expected returns and state‐price density parameters analogous to the diffusion case.